Chemical Constituents of the Flower Essential Oil of Lavandula officinalis Chaix. from Isfahan (Iran): Essential oil of Lavandula officinalis - Afsharypuor, Suleiman; Azarbayejany, Nahid (Iranian Journal of Pharmaceutical Sciences, 2006)
Chemical constituents of the essential oil of flowers of Lavandula officinalis Chaix. growing in Isfahan, Iran, were studied by TLC and gas chromatography-mass specrtometery (GC-MS) methods. Twelve components which constitute 94.8% of the examined oil were identified. The main constituents were linalool (34.1%), 1,8- cineole (18.5%), borneol (14.5%), camphor (10.2%), terpinen-4-ol (4.5%), linalyl acetate (3.7%), α-bisabolol (3%), α-terpineol (2.2%) and (Z)-β-farnesene (2.2%).